What Drives Islamic Banks Profitability in the Gulf Cooperation Council Countries? - Hichem Hamza (Türkiye İslam İktisadı Dergisi)
The purpose of this paper was to assess the profitability determinants of commercial Islamic banks in Gulf Cooperation Council (GCC) countries during the period 2005-2019. The literature review reveals the lack of consensus on the fundamental Islamic banking profitability drivers in these countries considered as the core of the Islamic banking industry in the world. This paper, therefore, considered the most potent factors that might influence the profitability of Islamic banks in countries that rely on a dual banking system. This study used the panel data methodology and Generalized Method of Moments (GMM) estimation with a robustness check. The results reveal that the Islamic banks profitability is strongly influenced by the assets quality, deposits position and cost efficiency. The sizable Islamic banks are not the most robust in profits generation and therefore a reduced size could be recommended for profitability. The capitalisation does not play a crucial role in profitability which might support the tendency of Islamic banks to the leverage-based financing strategy. The effect of the crisis is for the most part evident, which makes the Islamic banks stability view questionable during a crisis period. Liquidity is not determinant for the Islamic banks profitability. Similar results were reached for the macroeconomic variables, which highlights the weak relationship of Islamic bank profitability with the real economy.